An evaluation on Strategic Plan of Transformation in Vocational Education (SPTVE) 2011-2025 and its relevance towards the thrive of 4th industrial revolution - Mustakim, Siti Salina; Sulaiman, Tajularipin; Abdul Manaf, Umi Kalthom; Minghat, Asnul Dahar; Rabindarang, Siva (Pennwell Corporation, 2020)
The revolution of 4IR and its crucial importance along with current development in education necessitates the development of relevant competencies among Technical and Vocational Education and Training (TVET) teachers. The primary aim of this study is to (1) determine the relationship between Pedagogical Skills & Knowledge, Teaching & Pedagogical Training, and Difficulties Encountered by Teachers with TVET teacher’s profiling, and (2) explore the development of Pedagogical Skills & Knowledge and Teaching & Pedagogical Training among TVET teachers in the implementation of SPTVE 2011-2025. Data is collected from a survey and case studies. 24 Technical institutions that offer Technology Electronic Courses are selected based on a stratified random sampling procedure. A total number of 137 respondents are selected for the survey, and two Institutions are selected purposively for the case studies. This study contributes to the development of a framework for professional competencies among TVET teachers to respond to the development of 4IR along with the implementation of SPTVE 2011-2025.